New Proposed Dose of Irradiation to Control Fruit Flies (Diptera:Tephritidae) and its Influence to Super Red Pittaya (Hylocereus costaricensis) Quality - Hendra Adi Prasetia; Slamet Budiawan; Salbiah; Ade Syahputra; Murni Indarwatmi; Wayan Murdita (Bogor Agricultural University, Indonesia, 2023)
As one of the important pests, fruit flies derived from Tephritidae family have caused the worst consequences in losing the economic value of fresh horticultural commodity including on the dragon fruits. As a prospective quarantine treatment, gamma irradiation has been thrived to eliminate totally the appearance of those adults’ flies with less impact on the fruit quality degradation. In this study, a series of irradiation dosages were examined to both the third instar larvae (subsequently from Bactrocera papayae, B. cucurbitae and B. carambolae) infesting fruits and the non-infested ones afterwards at 0, 50, 100, 150, 200, 250, 300, 350 and 400 Gy. For a number of the infested fruits, a series of observations were persisted in at room temperature (27±1°C) until two weeks of the post-treatment period. Whereas the non-infested fruits were stored at 11±1°C for 17 days of the storage. Results showed that B. papayae required the highest recommended dosages (the effective dose = 248.4 Gy; the minimum dose = 225.1 Gy; the maximum dose = 279.6 Gy) for achieving LD0.99 rather than the other tested spesies. There were also no significant differences among each of the non-infested fruits in terms of altering of the observed physical attributes. This result has become a distinct indication that a higher dose value than the generic one is mostly recommended both for phytosanitary irradiation and stabilization of fruit quality.